O efeito da reat??ncia na satisfa????o com o conv??nio m??dico: uma an??lise por modelagem de equa????es estruturais - Rafael, Diego Nogueira (2016)
Currently the Brazilian health system is complex, the constitution guarantee of care to the health care of all individuals within the national territory, and the State through the Unified Health System (SUS) is responsible for this difficult task. In this context, where the state is unable to serve the entire population, private organizations have taken part in this market, offering health plans and private assistance, which is called supplementary health. In this context, the themes studied are the psychological reactance that means the negative emotional reaction generated by the total or partial lack of freedom or the expectation of freedom of an individual who once got it and the health plan user???s satisfaction. User satisfaction and psychological reactance are topics exhaustively studied by the organizations, being one of the preferred themes in the study of consumer behavior, evidently being relevant because these studies allow the strategic analysis of the companies with more accurate data, resulting in greater profitability and success of these institutions. The study was conducted by means of a quantitative method, based on the satisfaction and psychological reactance of the users of the supplementary health system with the modeling of structural equations using the SmartPLS system, in order to test the hypotheses constructed based on the theories studied. The results obtained are in agreement with the theory of reactance and satisfaction, confirming the hypotheses proposed, there being a negative relation between both for the studied sample, the lower the reactance level observed, the higher the satisfaction level declared by the users. The conclusion of the study suggests as a contribution to the practice that managers approach the relationship between health plans and their users, creating programs to prevent diseases, combat sedentarism, chronic diseases and improve the quality of life of users, obtaining a participation collaborative of both.